2011
DOI: 10.1039/c0dt01637c
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura cross-coupling coupling reactions with low catalyst loading: a green and sustainable protocol in pure water

Abstract: The Suzuki-Miyaura coupling reaction represents one of the most important synthetic transformations developed in the 20th century. However, the use of toxic organic solvents remains a scientific challenge and an aspect of economical and ecological relevance, and benign water as a reaction medium was found to be highly effective to overcome some of these issues. In the present manuscript, we described Suzuki-Miyaura coupling reactions in neat water, without using any phase transfer reagent. Notably, this protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…The reaction using 1.0 © 10 ¹3 mol % of the precatalyst C-N-C complex 2 afforded the product in 5% yield ( Table 1, Entry 5), whereas the reaction using the same quantity of C-C-N complex 1 gave the desired product in 75% yield with a turnover number (TON) value of 75,000 (Table 1, Entry 2). The TON value for 1 is relatively high but still lower than the reported values (770,000 14 and 800,000 6b ) for similar reactions in water. A smaller amount of 1 (1.0 © 10 ¹4 mol %) caused the yield to drop to 6% (Table 1, Entry 3).…”
Section: Resultsmentioning
confidence: 72%
“…The reaction using 1.0 © 10 ¹3 mol % of the precatalyst C-N-C complex 2 afforded the product in 5% yield ( Table 1, Entry 5), whereas the reaction using the same quantity of C-C-N complex 1 gave the desired product in 75% yield with a turnover number (TON) value of 75,000 (Table 1, Entry 2). The TON value for 1 is relatively high but still lower than the reported values (770,000 14 and 800,000 6b ) for similar reactions in water. A smaller amount of 1 (1.0 © 10 ¹4 mol %) caused the yield to drop to 6% (Table 1, Entry 3).…”
Section: Resultsmentioning
confidence: 72%
“…Reactive solvated complexes may be formed in the course of organic reactions using Pd catalysts, such as some cross-coupling reactions of organic molecules. Recently it has been reported that decreasing the amount of the Pd-catalyst considerably enhanced the turnover numbers of cross-coupling reactions and that reactions at a higher concentration of the catalyst gave lower yields as seen in the catalyst concentration dependent cross-coupling reactions [64,65], where the proposed solvated complex intermediate may be also involved.…”
Section: Metal-aromatic Ring σ-Bonding Complexesmentioning
confidence: 96%
“…Metal-indole reaction intermediates may become important especially in the field of organic chemistry [64][65][66], and some biological compounds and drugs, such as tryptophan tryptophylquinone [67] and an anti-inflammatory agent indomethacin [68], have the indole moiety as an essential component. Useful C-C bond formation reactions have been developed by using metal complexes, especially Pd complexes.…”
Section: Metal-aromatic Ring σ-Bonding Complexesmentioning
confidence: 99%
“…10 -4 mol% Pd, 40 after Suzuki coupling. Both C 1s spectra display a peak at a binding energy of 288.6 eV, which is not present before coupling (Supporting Information, Figure S1) and can be assigned to the presence of an aromatic fluoride group (=C-F) 45 .…”
Section: Suzuki Coupling On Si(100)mentioning
confidence: 99%